Evaluation of Quality Control System on Audit Performance (Case Study of BPK Representative of West Sulawesi Province) - Agusmansyah Agusmansyah; Dwi Martani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to evaluate the quality control system (SPM) for the performance of the audit carried out at the BPK Representative of West Sulawesi Province. The six components in the audit performance analyzed are audit planning, audit implementation, supervision & review, reporting of audit results, follow-up monitoring of audit results, and audit evaluation to determine its implementation. In addition, this study will also provide recommendations to improve the effectiveness of the implementation of SPM. This study used qualitative descriptive analysis by evaluating SPM implementation documents and the results of interviews with SPM implementers and SPM assessors. The results of this study show that overall, the BPK Representative of West Sulawesi Province has implemented a quality control system but, in its implementation, it is still necessary to consider improving the understanding of SPM for auditors, fulfilling the shortage of auditors in the composition of the Audit Team, proposing a quality management system on the component of monitoring follow-up audit results, and strengthening supervision on the implementation of SPM.